2016
DOI: 10.1155/2016/2962047
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Approach for Lung Segmentation with Juxta-Pleural Nodules from Thoracic CT Based on Contour Tracing and Correction

Abstract: This paper presents a fully automatic framework for lung segmentation, in which juxta-pleural nodule problem is brought into strong focus. The proposed scheme consists of three phases: skin boundary detection, rough segmentation of lung contour, and pulmonary parenchyma refinement. Firstly, chest skin boundary is extracted through image aligning, morphology operation, and connective region analysis. Secondly, diagonal-based border tracing is implemented for lung contour segmentation, with maximum cost path alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In similar studies, it is shown that auto-contouring techniques can save time [16,17], while other studies show promising new techniques that could potentially save time if investigated [10,18]. Young et al showed a potential time save for contouring lymph node for pelvic cancer patients [19].…”
Section: Discussionmentioning
confidence: 98%
“…In similar studies, it is shown that auto-contouring techniques can save time [16,17], while other studies show promising new techniques that could potentially save time if investigated [10,18]. Young et al showed a potential time save for contouring lymph node for pelvic cancer patients [19].…”
Section: Discussionmentioning
confidence: 98%
“…In order to alleviate this problem, In the energy optimization method, people usually convert the segmentation task into an energy minimization task to process. For example, in [22][23][24][25], the author uses a level set function to characterize the image, and when the segmented contour matches the nodule boundary, the energy function reaches a minimum. A similar approach is the lung nodules segmentation method based on shape prior hypotheses and level sets, proposed by Farag et al [7].…”
Section: Related Workmentioning
confidence: 99%
“…At present, there are various ranges of techniques implemented for segmentation. The work carried out by Wang and Guo [11] have presented a combined implementation of identifying skin boundary, segmenting contour regions, and refinement of lung region. Most recently, a unique segmentation process of segregating heart from the lung field was introduced by Dai et al [12].…”
Section: Related Workmentioning
confidence: 99%